2012
DOI: 10.4321/s0213-61632012000200004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of attention-deficit/hyperactivity disorder and co-morbid disorders among students of Cumhuriyet University

Abstract: TURKEYABSTRACT -Background and Objectives: Most of the previous studies investigated prevalence of attention-deficit/hyperactivity disorder (ADHD) among university students with self report measures. Present study investigated actual prevalence of ADHD and comorbid disorders among university students in Cumhuriyet University of Sivas in Turkey.Methods: In the first stage, 980 university students filled in the Adult ADHD Self-Report Scale and socio-demographic form, 79 of whom were above the cut-off score of Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 33 publications
2
11
2
Order By: Relevance
“…Overall, these studies show that between 0% and 21.8% of tertiary students report clinically significant symptoms associated with ADHD, and inattention has consistently been the most commonly endorsed ADHD-related symptom (DuPaul et al, 2001;Harrison, Alexander, & Armstrong, 2013;Kavakci et al, 2012). This variability in rates of selfreported symptoms is attributed to the different measures utilized, each with their own symptom threshold and criteria for clinical significance.…”
Section: Previous Estimates Of Adhd In University Studentsmentioning
confidence: 94%
See 2 more Smart Citations
“…Overall, these studies show that between 0% and 21.8% of tertiary students report clinically significant symptoms associated with ADHD, and inattention has consistently been the most commonly endorsed ADHD-related symptom (DuPaul et al, 2001;Harrison, Alexander, & Armstrong, 2013;Kavakci et al, 2012). This variability in rates of selfreported symptoms is attributed to the different measures utilized, each with their own symptom threshold and criteria for clinical significance.…”
Section: Previous Estimates Of Adhd In University Studentsmentioning
confidence: 94%
“…This is further supported by Garnier-Dykstra, Pinchevsky, Caldeira, Vincent, and Arria (2010) who in a sample of 1,080 university students found that 10.3% of the entire sample scored in the clinical range on the ADHD Self-Report Scale (ASRS), while only 2% of students reported a formal diagnosis of ADHD. In a study of 980 Turkish university students, 10.1% reported ADHD traits on the ASRS v1.1, while only 6.1% had a diagnosis (Kavakci et al, 2012).…”
Section: Previous Estimates Of Adhd In University Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps, in half of the children with ADHD symptoms, this disorder appears in adulthood (Ivanov & Yehuda, 2014;Klein et al, 2012). ADHD occurs in 3-7% of schoolage children and 4% of adults (Faraone & Antshe, 2008;Kavakci, Kugu, Semiz, Meydan, Karsikaya, & Dogan, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A study suggest that among half of individuals, the symptoms become more visible during the adulthood (Ivanov & Yehuda, 2014;Klein et al, 2012). Other studies suggest that ADHD is common among school going children where almost 7% of school going children caught this disease while among 4% of population of adult is also subject to ADHD (Faraone & Antshe, 2008;Kavakci, Kugu, Semiz, Meydan, Karsikaya, & Dogan, 2012). Adult individuals who have ADHD face several problems such as difficulty in time management, less extent of social adjustment, lack of interpersonal and communication skills, execution action problems, emotional and psychological problems, attention deficit disorder, work and educational challenges, relationship challenges, and drug and alchol abuse problem (Bakhshani, Raghibi, & Babaei, 2011;Green & Rabiner, 2016).…”
mentioning
confidence: 99%